Memory in the Burst Occurrence of Repeating Fast Radio Bursts - Wang, Ping; Song, Li-Ming; Xiong, Shao-Lin; Zhao, Xiao-Yun; Wang, Jin; Zhao, Shu-Min; Xiao, Shuo; Cai, Ce; Xie, Sheng-Lun; Xue, Wang-Chen; Wang, Chen-Wei; Wang, Yue; et al. (The Astrophysical journal, 2024)
Understanding the nature of repeating fast radio bursts (FRBs) is crucial for probing their underlying physics. In this work, we analyze the waiting time statistics between bursts of three repeating FRBs from four data sets. We find a universally pronounced dependency of the waiting times on the previous time interval (denoted as λ 0 ). We observe a temporal clustering, where short waiting times tend to be followed by short ones and long by long, comparative to their mean value. This memory dependency is manifested in the conditional mean waiting time as well as in the conditional mean residual time to the next burst, both of which increase in direct proportion to λ 0 . Consequently, the likelihood of experiencing a subsequent FRB burst within a given time window after the preceding burst is generally influenced by the burst history. We reveal, for the first time, that these memory effects are present in the scale-invariant preconditioned waiting time distribution. We show that the memory effect provides a unified description of waiting times that may account for both the repeating FRBs and the apparently nonrepeating FRBs (i.e., those only observed one time). These results shed new light on the mechanism of FRBs.